Tingkat Kepuasan Nasabah Tabungan Sikoci Kasus Bank Nagari Cabang Pembantu UNP Padang - Saiful Anwar; Jhon Fernos (JURNAL PUNDI, 2018)
Analysis of Customer Satisfaction with Sikoci Savings at Bank Nagari Sub-Branch of UNP, to find out how satisfied the customers of Sikoci Savings, especially students, are in the facilities and facilities provided.  Sikoci Savings is Student Savings to get Student Identity Cards and ATMs, which can be used as SPP payments in any Bank Nagari ATM machine and as other financial transactions, which can facilitate students in paying tuition fees or SPP and other financial transactions.The method analysis statistic descriptive quantitative data collective from students UNP who have SIKOCI saving with non probability sampling use accidental sampling of 25 respondent July 2017. This research find from 5 dimention service quality generallay good but need improvement to maximize it. Keywords: Customer Satisfaction, Savings